Effectiveness and adverse drug reactions of levetiracetam and midazolam in refractory neonatal seizure: A cross-sectional comparative study - Diptiman Jayswal; Uttam Kumar Roy; Taraknath Ghosh; Purnendu Mandal (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Neonatal seizure (NS) reflects serious underlying brain injury, requiring immediate evaluation and early treatment. In neonates, phenobarbitone and phenytoin are used primarily to control the seizures. If uncontrolled, widespread off-label use of midazolam and levetiracetam was practiced. These drugs gained popularity though there are no such studies available on literature search comparing them. The present study was designed to explore these lacunae using these two drugs in refractory cases. To study the efficacy and adverse drug reactions (ADRs) of midazolam and levetiracetam not responding to usual line of therapy. MATERIALS AND METHODS: This was a prospective cross-sectional study conducted on 69 neonates in the NICU and Department of Pharmacology in Burdwan Medical College and Hospital, West Bengal. Patients receiving midazolam or levetiracetam when uncontrolled with first line antiepileptics, namely, phenobarbitone and phenytoin, were considered eligible. The study variables were time to control seizure, seizure recurrence and frequency, and treatment-related adverse events. analysis used Mann-Whitney U-test were applied Comparison with respect to time to control and Chi-square test were applied to detect difference in proportion for ADRs. The SPSS Statistics 17.0 was used for analysis. RESULTS: We compared the time periods to control neonatal seizure for effectiveness between levetiracetam and midazolam showing no significant difference (P = 0.190). Comparing the portion of recurrences in two groups gives statistically nonsignificant (P = 0.878) result. Only respiratory depression was seen in the levetiracetam group (12.90%) and midazolam group (18.42%). All adverse events were 'probable' as per the WHO-UMC criteria, and there was no statistically significant difference between the two drugs (P = 0.533). CONCLUSIONS: Both midazolam and levetiracetam are equally effective and safe in NS not responding to usual line of treatment.